Contraception, reproductive health and pregnancy outcomes among women exposed to intimate partner violence in Nigeria - Okenwa, Leah; Lawoko, Stephen; Jansson, Bjarne (The European Journal of Contraception & Reproductive Health Care, 2011)
To examine the association between reproductive health practices/outcomes and exposure to intimate partner violence (IPV) among women in Nigeria. More specifically, the association between IPV and use of contraception; miscarriages, induced abortions, stillbirths, and infant mortality; and having many children, was assessed. Methods Data on studied variables were retrieved from the Demographic and Health Surveys of Nigeria 2008, a nationally representative sample of 33,385 women of reproductive age. IPV was defined as exposure to physical, sexual or emotional abuse. The association between contraception use, pregnancy outcomes and infant mortality, and exposure to IPV was assessed using the chi-square test for unadjusted analyses. To control for potential confounding, socio-demographic variables were adjusted for using multiple logistic regression. Results Compared with women not exposed to IPV, those who were, exhibited a higher likelihood of using modern forms of contraception; having a history of miscarriages, induced abortions, stillbirths, or infant mortality; and having many children. The aforementioned observations still stood after adjustment for potential confounders (e.g., demographic and socioeconomic factors). Conclusion Though causal inference cannot be drawn due to the cross-sectional design, the study has important implications for incorporation of IPV detection and management in initiatives aimed at improving women’s reproductive health.
Keywords: Intimate partner violence; Contraception; Reproductive health outcomes; Nigeria